Counsel for a person who is not a party to a criminal proceeding (Ius Novum, 2025)
The study analyses the issue of the availability of a counsel at law to persons who are not parties to criminal proceedings. It refers not only to the catalogue of entities authorised to appoint a counsel, but also to the grounds for refusing to allow such counsel to participate in procedural activities. Separate considerations are devoted to the issue of the procedure for participation of a counsel in a proceeding. In the final conclusions, de lege ferenda, it is proposed that the scope of the right to a counsel should be differentiated and should be made dependent on the level of protection of the interests of persons who are not parties.
Keywords: right to a counsel, counsel at law, person who is not a party, suspect, interest of a participant in a criminal proceeding